Dematel digraph: A decision making tool for project practitioners and researchers during covid-19 pandemic - Lee, Chia Kuang; Tay, Joo Hui; Liew, Siau-Chuin (2021)
DEMATEL DIGRAPH is a new invention that generates directed graph (Digraph) based on DEMATEL (Decision Making Trial and Evaluation Laboratory) algorithm. Helps students and project practitioners in solving complex decision problems, identifying critical risks and analyzing causeeffect chain components of a complex system.